The new artistic language of Kazakh architecture based on the cultural heritage of the ancestors - Duysebay, E.K.; Duysebay, Е.Е. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Today, at the beginning of the 21st century, the meaningful expression of the image of architecture or artistic language is a key indicator of the competitiveness of the country’s culture and the competitiveness of the state itself in the global world. A unique architecture requires great intellectual and creative efforts. The results of the fundamental scientific program "Cultural Heritage" should be taken into account in the development process of the ethnocultural aesthetics concept of our architecture. The research results published in this article represent an investment in culture and creativity such as the revival of public consciousness through the harmonious introduction of the best national traditions and aesthetic preferences into the new architecture. The result of scientific research is the ethnocultural concept of the architectural image, realized through the synthesis of ethnocultural pictorial traditions with technical achievements and digital technology. The archaic brutal composition of the Scythian art and the bionic plasticity of the Kazakh ornamental art will become the formative and structural components of the new Kazakh architecture. A new interpretation of modern architecture allows architects to take a fresh look at the artistic tasks of creativity. The originality and recognizability of architecture raise the level of the aesthetic outlook and artistic taste of society and makes the aesthetic appearance of our cities more targeted.